Ecological Humanization in Iraqi Feminist Poetry A study in the light of Environmental Criticism - Hussain Allawi Taher , Assist. Lect . Asma; أ.م.د. عبد الرحمن عبد الله أحمد (Basra studies journal, 2026)
The present research concerned with the study of ecological humanization as one of the philosophical visions and ideas that deal with the relationship of man with the environment and the ethical issues branching from it, on which environmental criticism is built. The research focused on clarifying the concept of environmental criticism, as one of the post-modern critical approaches that originated in Western cultural studies and emerged from it, environmental criticism concerned with the study of the relationship between literature and nature. The research tried to employ ecological humanization to expose how to represent nature as a living and active organism, human participation with existence and suffering. Humanization is represented as a reaction to the humanism of modernity, which takes the centrality of man as its starting point, and makes nature a resource that can be exploited and controlled. The research dealt with contemporary feminist poetry in Iraq as an applied model for these concepts to determine the extent of the impact of human superiority, due to the central hegemony represented by the turbulent political reality experienced by Iraq, and the resulting wars, terrorism, killing, sabotage and displacement. The study of the environmental repercussions, resulting from these phenomena from the perspective of ecological humanization, whether environmental humanization or environmental brutality, has been monitored by research in some texts of Iraqi female poets.